Karakteristik Peleburan Material Mikro Pada Alat Penukar Kalor Tipe Cangkang-Pipa sussunan Staggered - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Thermophysic properties of micro material has been investigated using several tester equipment, i.e. DSC (Differential Scanning Calorymetry) made by Mettler, Thermal Conductivity Meter model TC-31, Picnometer, Hydrometer, and viscometer, were used as test materials on a melting process with heat flux of heater surface, on staggered tubes bank of shell and tube type heat exchanger. Based on the data of thermophysic properties and the temperature of materials as the test result, melting characteristics were obtained in the form of a heat transfer coefficient as a function of time, modus of dominant heat transfer along melting process, and Nusselt number correlation. Theoretical analysis was used as a comparative of the test result, i.e. a numerical calculation by using an explicit formulation. The result of the research shows that along melting process, conduction is a modus of dominant heat transfer, and there was suitability between melting test result and theoretical analysis.